2016
DOI: 10.1111/vsu.12535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Methicillin‐Resistant Staphylococcus pseudintermedius Biofilm Formation on Antimicrobial Susceptibility

Abstract: The MIC for biofilm-associated S. pseudintermedius are significantly higher than for planktonic bacteria. Standard methods for determining MIC are not appropriate for biofilm-associated infections. This must be considered when determining treatment regimens for infections that potentially involve biofilms, and further study of methods to control biofilm-associated infections is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…This positioning, combined with the dog's incontinence, almost certainly played a role in the development of urinary tract infection within a month of surgery. While resolution of urinary tract infection has been reported after subcutaneous ureteral bypass in cats, biofilm formation can make clearance challenging . Even if infection could be cleared, the positioning of implants for the dog in this study would have predisposed to reinfection.…”
Section: Discussionmentioning
confidence: 91%
“…This positioning, combined with the dog's incontinence, almost certainly played a role in the development of urinary tract infection within a month of surgery. While resolution of urinary tract infection has been reported after subcutaneous ureteral bypass in cats, biofilm formation can make clearance challenging . Even if infection could be cleared, the positioning of implants for the dog in this study would have predisposed to reinfection.…”
Section: Discussionmentioning
confidence: 91%
“…Further studies are needed to clarify the penetration and killing mechanisms. However, these findings might be of therapeutic interest because biofilm significantly affects antimicrobial susceptibility of both MSSP and MRSP from dogs [7]. Of interest, human S. pseudintermedius isolates also form structurally complex biofilm that are intrinsically resistant to antibiotics [34], thus complicating zoonotic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation can facilitate the colonization of different body sites in dogs and hinder the infection treatment. Walker et al reported MIC values for biofilm-associated S. pseudintermedius significantly higher than for planktonic bacteria [7]. In another study, Meroni et al reported that 68% of S. pseudintermedius isolates were able to form biofilms, but 100% of the multidrug resistant strains were slime producers; therefore, it seems that biofilm production can facilitate bacteria horizontal gene transfer [8].…”
Section: Introductionmentioning
confidence: 99%
“…While concern over resistance to topically used antibacterial agents exists, clinical treatment failure of topical anti-staphylococcal therapy has not been conclusively reported, to the authors' knowledge; MICs for staphylococci from animals have been consistently low and are likely to be substantially exceeded by achievable topical drug concentrations (Loeffler et al 2008;Valentine et al, 2012;Clark et al, 2015). However, continual monitoring of resistance and clinical efficacy, further evaluation of alternatives such as hypochlorite (bleach), Manuka honey, of potentially synergistic combinations and of anti-biofilm products will be critical (Walker et al, 2016).…”
Section: Topical Therapymentioning
confidence: 99%